RNA interference : application to drug discovery and challenges to pharmaceutical development - Johnson, Paul H., 1943- (Hoboken, N.J. : Wiley, 2011)
'RNA Interference: Application to Drug Discovery and Challenges to Pharmaceutical Development provides a general overview of this rapidly emerging field, with a strong emphasis on issues and aspects that are important to a drug development team. The first part covers more general background of RNA interference and its application in drug discovery. In the second part, the book addresses siRNA (small interfering RNA), a pharmaceutically potent form, and its use and delivery in therapeutics along with manufacturing and delivery aspects'--Provided by publisher.
(Publisher-supplied data) RNA interference: What is it? / James A. Birchler -- Nucleic acids as regulatory molecules / Faqing Huang, CJ Yu, and Yanlin Guo -- Use of siRNA oligonucleotides to study gene function / Kristin A. Wiederholt and Adam N. Harris -- Genome scanning by RNA interference / Roderick L. Beijersbergen and Oliver C. Steinbach -- Discovery of new siRNA delivery agents / Paul H. Johnson, Diane Frank, Kunyuan Cui, Roger Adami, Harry Wang, Michael Houston, and Steven C. Quay -- In vivo Delivery of siRNA: challenges and strategies / Aliasger K. Salem and Mark A. Behlke -- Interferon, cytokine induction and other potential in vivo toxicities / Adam Judge, Marjorie Robbins, and Ian MacLachlan -- Application of RNA interference to viral diseases / Ralph A. Tripp and Stephen Mark Tompkins.
Includes bibliographical references and index.
Keywords: RNA Interference; Drug Discovery